Self-Identity and Career Success of Nurses in Infectious Disease Department: The Chain-Mediating Effects of Cognitive Emotion Regulation and Social Support - Wu, Chao; Li, Shuang; Cheng, Feixia; Zhang, Linyuan; Du, Yanling; He, Shizhe; Lang, Hongjuan (Frontiers in Psychology, 2020)
There have been some researches which are conducted regarding to nurses’ career success and aim at exploring its influencing factors, but there is no research on the the mechanism of self-identity on career success of infection control nurses. In order to further explore the formation mechanism of career success of nurses, we conducted our study using the Kaleidoscope Career Model to explore the chain mediating effects of cognitive emotion regulation and social support between self-identity and career success. Five hundred and forty-seven infection control nurses from nine different hospitals participated in the study and completed the questionnaires of Self-identity Scale, Cognitive Emotion Regulation Scale, Social Support Scale, and Career Success Scale. The results of structural equation modeling revealed that self-identity had a positive effect on positive emotion regulation and social support, and a negative impact on negative emotion regulation. Positive (negative) emotion regulation had a positive (negative) effect on social support. And all antecedents had a positive impact on career success, except negative emotion regulation, which had a negative one. Bootstrap analysis showed that the relationship between self-identity and career success was partially mediated by the chain of cognitive emotion regulation and social support. Overall, our research shed light on the mechanism of self-identity on career success of nurses. Theoretical and practical implications were discussed.